Why do people still live in East Germany? - Jennifer Hunt (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
In 1997 GDP per capita in East Germany was 57% of that of West Germany, wage rates were 75% of western levels, and the unemployment rate was at least double the western rate of 7.8%. One would expect that if capital flows and trade in goods failed to bring convergence, labor flows would respond, enhancing overall efficiency. Yet net emigration from East Germany has fallen from high levels in 1989-1990 to close to zero. Using state-level data for all of Germany, available from 1991-1996, I am able to explain the downward trend in east to west migration using wage and unemployment information. Convergence in hourly wages is the most important factor. Analysis of the eastern sample of the German Socio-Economic Panel for 1990-1997 suggests that commuting is unlikely to substitute substantially for emigration. The individual-level data further indicate that emigrants are disproportionately young and skilled, and that individuals suffering a layoff or non-employment spell are also much more likely to emigrate.
Keywords: 330; Binnenwanderung; Regionale Arbeitslosigkeit; Regionale Lohnstruktur; Schätzung; Deutschland